Assessment of Solar and Wind Energy Resources at Five Typical Locations in Sarawak - Jakhrani, A.Q.; Othman, A.K.; Rigit, A.R.H.; Samo, S.R. (Universiti Tenaga Nasional, 2012)
This paper investigates the accessibility and potential of solar and wind energy resources at five typical locations in Sarawak. The availability and status of solar and wind power potential is ascertained by various environmental factors, such as solar radiation, wind speed, air temperature and pressure, humidity, amount of rainfall and cloud cover. The acquired data of selected locations namely Kuching, Sri Aman, Sibu, Bintulu, and Limbang, was systematically evaluated. The quantity and magnitude of available solar and wind energy resources has been estimated by the determination of required parameters from different climatic variables. It is intended that these results could be used as input data for the simulation of a standalone photovoltaic-wind power system for the estimation of annual energy production based upon the local meteorological conditions and the characteristics of the hybrid system.